The recurrence relation above has the initial condition of . Suppose we define the function Find the value of .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is given that:
a n + 1 ⇒ a n ⇒ a n = 2 n a n = 2 ( n − 1 ) a n − 1 = 2 2 ( n − 1 ) ( n − 2 ) a n − 2 = 2 3 ( n − 1 ) ( n − 2 ) ( n − 3 ) a n − 3 . . . . . . . . . = 2 n − 1 ( n − 1 ) ( n − 2 ) ( n − 3 ) . . . . ( 3 ) ( 2 ) ( 1 ) a 1 Since a 1 = 1 = 2 n − 1 ( n − 1 ) !
Therefore,
S ( x ) = n = 1 ∑ ∞ a n x n = n = 1 ∑ ∞ 2 n − 1 ( n − 1 ) ! x n = x n = 1 ∑ ∞ 2 n − 1 ( n − 1 ) ! x n − 1 = x n = 0 ∑ ∞ n ! ( 2 x ) n = x e 2 x
⇒ ∫ 0 2 S ( x ) d x = ∫ 0 2 x e 2 x d x By integration by parts = [ x 2 e 2 x ] 0 2 − ∫ 0 2 2 e 2 x d x = 4 e − [ 4 e 2 x ] 0 2 = 4 e − 4 e + 4 = 4